2018
DOI: 10.1039/c8sm00210j
|View full text |Cite
|
Sign up to set email alerts
|

Rubber materials from elastomers and nanocellulose powders: filler dispersion and mechanical reinforcement

Abstract: Rubber materials with well-dispersed fillers and large mechanical reinforcement have been obtained by melt-processing a diene elastomer matrix and tailored nanocellulose powders having both a high specific surface area and a modified interface. Such filler powders with a specific surface area of 180 m2 g-1 and 100 m2 g-1 have been obtained by freeze-drying suspensions of short needle-like cellulose nanocrystals (CNCs) and entangled networks of microfibrillated cellulose (MFC) in tert-butanol/water, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…While in most of the reported works, hand layup method, melt mixing, and solution casting are followed for CNC loading. [21][22][23][24][25] Therefore, the effect of surface modification on CNC dispersion through two roll mixing is presumed to be validated in the present investigation. Surface modification of CNC is done following a reported method where isocyanatepropyltriethoxysilane is employed.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…While in most of the reported works, hand layup method, melt mixing, and solution casting are followed for CNC loading. [21][22][23][24][25] Therefore, the effect of surface modification on CNC dispersion through two roll mixing is presumed to be validated in the present investigation. Surface modification of CNC is done following a reported method where isocyanatepropyltriethoxysilane is employed.…”
Section: Introductionmentioning
confidence: 96%
“…21 Fumagalli's group reported melt-processing of a diene elastomer with 3,3 0 -dithiopropionic acid chloride and palmitoyl chloride tuned nanocellulose powders which showed a high specific surface area with a modified interface. 22 Thomas et al used zinc-modified CNCs to achieve better dispersion in the NR matrix and very good tensile strength thereby. 23 There are also some reports on CNC based NR composites where achieving adequate reinforcement remains an issue.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that 3,3'-dithiopropionic acid chloride (DTACl) modified cellulosic nanocrystals (CNC) can covalently bound to styrene-butadiene rubber (SBR) effectively [15]. The homogeneous dispersion of DTACl modified cellulose nanocrystals provides an additional strain stiffening effect which was similar to the behavior exhibited by silica and carbon black in elastomers.…”
Section: Introductionmentioning
confidence: 98%
“…Fumagalli et al [26] researched the potential of surface-modified CNCs and CNFs with 3,3′-dithiodipropionic acid chloride (DTACl) in SBR. They reported the occurrence of a reactive interface and strong stiffening behavior with the addition of the modified nanofillers.…”
Section: Nanocellulose-reinforced Synthetic Rubber Compositesmentioning
confidence: 99%
“…The search for substitutes and alternatives of conventional fillers for rubber applications is the driving force in research and development sectors in rubberbased research groups and large-scale industries. Recent advances show the prowess of nanocellulose in achieving or surpassing the current reinforcing performance of conventional fillers [25,26].…”
Section: Introductionmentioning
confidence: 99%